Understanding primary carers' occupational adaptation and engagement. (1st September 2013) - McDougall, Carmel; Buchanan, Angus; Peterson, Sunila
<x xml:space="preserve">Abstract</x> Background/aim Primary carers for people with intellectual disability living in remote rural areas experience high demand care commitments that may require them to be available twenty‐four hours seven days a week and reduce their access to formal or respite support leaving them little time to engage in other occupations. The aim of this study was to explore the impact of caring for a person with an intellectual disability living in remote rural farming location on primary carers' occupational engagement. Method A thematic analysis, using an interpretive phenomenological analysis approach, was conducted on seven in‐depth semi‐structured interviews of primary carers. Results Occupational adaptation and engagement, emerging as a primary theme, indicated that primary carers' occupations were affected by: limiting opportunity to develop occupations; developing new occupations; adapting occupations; and ceasing occupations. A number of influencing themes, affecting the primary carers' occupational engagement also emerged, including: lifestyle and occupational roles; wellness and health; engaging quality supports; societal and community context; and vision for the future. Conclusion The results provided an initial understanding of the impact of caring on the primary carers' occupational adaptation and engagement, and a suggestion that clinicians consider using a family‐centred approach as an effective and meaningful intervention.